(untitled) (CIPEEX, 2022)
THE TEAM BASED LEARNING (TBL) IS AN ACTIVE METHODOLOGY TOOL USED IN TEACHING LEARNING PROCESS TO EMPHASIZE THE MAIN POINTS OF CONTENT AND ITS PRACTICAL APPLICATION (MICHAELSEN, SWEET; 2008). THE TRADITIONAL TEACHING METHODS ARE FOCUSED ON TRANSFERRING KNOWLEDGE FROM TEACHER TO STUDENT, AND THEY ARE LIMITED TO PURELY TECHNICAL EDUCATION (MITRE ET AL., 2008). THESE METHODOLOGIES ARE LIMITED IN TERMS OF TEACHING CLINICAL REASONING SKILLS, TEAMWORK AND PERSUASIVENESS (MARQUES, ET AL., 2018). THE TBL WAS WAS USED IN THE CONTENT REVIEW WEEK WITH THE AIM OF IMPROVING CONTENT RETENTION AND TRAINING STUDENTS TO PERFORM CLINICAL REASONING. THIS IS A CASE REPORT OF THE TBL APPLICATION IN FOUR SUBJECTS OF UNIEVANGLICA€™S NUTRITION COURSE BETWEEN THE FIRST AND SECOND SEMESTERS OF 2022. THE METHODOLOGY WAS APPLIED IN ONE DISCIPLINE OF NUTRITION AND PUBLIC HEALTH, TWO DISCIPLINES ABOUT CLINICAL NUTRITION AND ONE DISCIPLINE ABOUT EXPERIMENTAL NUTRITION. IN ALL DISCIPLINES, QUESTIONNAIRES WERE APPLIED CONTAINING TEN OBJECTIVE QUESTIONS EACH. IN A FIRST MOMENT, THE STUDENTS HAD TO ANSWER THESE QUESTIONNAIRES INDIVIDUALLY, LIKE IN A TEST. THEN, THE STUDENTS WERE DIVIDED IN TEAMS, CONTAINING 4 OR 5 STUDENTS EACH TEAM. SO, AT THIS SECOND MOMENT THEY HAD TO ARGUE WITH THEIR PARTNERS ABOUT THE CORRECT ANSWER FOR EACH QUESTION, REACHING AN AGREEMENT ON WHAT WOULD BE THE RESULT IN THE TEMPLATE THAT REPRESENTED THE GROUP. AFTER THAT, THE THIRD STEP WAS TO RE-DISCUSS THE ANSWER WITH THE WHOLE CLASS (THROUGH THE REPRESENTATIVES ELECTED FOR EACH GROUP). AT THIS MOMENT, THE PROFESSOR ALSO PARTICIPATED IN THE DISCUSSION, DIRECTING THE STUDENTS TO THE CORRECT ANSWER. THIS METHODOLOGY WAS APPLIED TO REINFORCE SOME MORE RELEVANT CONTENT TO TEST, BESIDES TO HAVING QUESTIONS THAT REQUIRE CLINICAL REASONING TO SOLVE. FOR THAT PURPOSE, THE GROUP DISCUSSION IS VERY VALUABLE, ONCE IT PROMOTES THE OPENNESS TO LISTENING TO OTHER POINTS OF VIEW. THE EVALUATION OF THE CLASSES ON THE APPLICATION OF THE METHODOLOGY WAS POSITIVE, SINCE ACCORDING TO THE STUDENTS, THE ACTIVITY CONTRIBUTED TO THE FIXATION OF THE CONTENTS TAUGHT IN CLASS AND MADE THEM MORE PREPARED FOR THE TEST, SINCE IT TRAINED THEM TO PERFORM CLINICAL REASONING.